Estimating insect pest density using the physiological index of crop leaf - Chen, Meng; Liu, Xiang-Dong (Frontiers in Plant Science, 2023)
Estimating population density is a fundamental study in ecology and crop pest management. The density estimation of small-scale animals, such as insects, is a challenging task due to the large quantity and low visibility. Herbivorous insect is the big enemy of crops which often causes serious losses of crop. Feeding of insect results in changes in physiology-related chemical compositions of crop, but it is unknown whether these changes can be used to estimate population density of pest. The brown planthopper (BPH) Nilaparvata lugens is a serious insect pest hiding under rice canopy to suck sap of rice stems. BPH density is a crucial indicator for determining whether the control using pesticides will be carried out or not. Estimating BPH density is still dependent on man-made survey and light-trap methods which are time-consuming and low-efficient. Here we developed a new method based on physiological traits of rice leaves. Feeding of BPHs significantly decreased the SPAD readings and the contents of water, silicon, and soluble sugar of rice leaves. Four ratio physiological indices based on the SPAD, water, silicon, and sugar of the BPH-damaged rice leaves to these of healthy leaves were established, and they were significantly correlated with BPH density on rice plants. A rice growth stage-independent linear model based on the four ratio physiological indices and added other two variables, BPH damage duration and population increase rate, was developed which exhibited a reasonable accuracy for estimating BPH density. This new method will promote the development of density estimation of pest population towards non-professionalization and automatization.